BLUE OCEAN STRATEGY PENGEMBANGAN PARIWISATA DI PROPINSI KEPULAUAN BANGKA BELITUNG - Hamsani, Hamsani; Valeriani, Devi (JURNAL EKONOMI AKUNTANSI DAN MANAJEMEN, 2014)
As an area which has long been known as a tin, almost all economic activity depends on the tin industry. It is natural resources are not renewable, therefore, it should be thought for economy sector in support of the Bangka Belitung. Tourism is one of the sectors which have the potential for regional Bangka Belitung, bearing numerous tourist objects can be developed and packed; expected to contribute through tourist visits. The study is to analyze the development of tourism in the blue ocean strategy, is expected to provide inputs and become priority for stabilizing regional economy in the future. Things to be carried out, i.e. by the way subtract, create and enhance within the framework of a step in developing tourism in Bangka Belitung. The analysis method is applicable in the strategy is the ocean or the blue ocean namely creating the market without competitive and to let the no longer relevant.